OC-021 Flexible sigmoidoscopy completion rates. Time to change certification criteria?. (23rd September 2015) - Valliani, T; Dowler, K; Dunckley, P
Abstract : Introduction: The current JAG eligibility criteria for provisional certification in flexible sigmoidoscopy, state that the descending colon intubation rates should be >90%. This is also true for full certification in this procedure. However, a flexible sigmoidoscopy is often limited by a number of factors such as poor bowel preparation, achievement of clinical intention, patient discomfort and difficult sigmoid looping. In these circumstances, the descending colon is not intubated and it was felt that this occurred more than just 10% of the time. Therefore, we aimed to review 500 flexible sigmoidoscopies performed by independent endoscopists (nurse endoscopists, consultant gastroenterologist/surgeon and trainee gastroenterologist/surgeon) and assess the percentage of descending colon intubation as well as the limiting factors. Methods: All flexible sigmoidoscopies that were performed from January 2009 to June 2009 were reviewed. The endoscopist, the extent of the procedure, and the limiting factor(s) if the descending colon was not intubated were all recorded. Results: The majority of procedures (65%) were performed by a consultant and 54% of procedures (272/500) reached the descending colon. The independent nurse endoscopists were more likely to intubate the descending colon (72% intubation rate) than the consultant or independent trainee endoscopist. Out of the 46% (228/500) of procedures that did not reach the descending colon, the majority were limited by bowel preparation (36%). 25% did not complete the procedure as the clinical intention was achieved prior to reaching the descending colon and this decision was made by the performing endoscopist, who was a consultant in 93% of these cases. Other reasons include patient discomfort (11%), technical difficulty (stricture or tight bend)(7.5%), colitis (4%) and in a small number of cases, the patient had findings which warranted a full colonoscopy at another time in the future so would return for re-assessment. 12% (28/228) of the incomplete procedures had no clear reason as to why the procedure was abandoned. Only one of these patients had "moderate" discomfort recorded on the pain score and so pain did not seem to be a limiting factor. Conclusion: The current JAG certification criteria for flexible sigmoidoscopy are under review and the data here suggest that the descending colon intubation rate of >90% is inappropriate as an eligibility criterion for certification. One of the reasons that the descending colon intubation rate is lower for a consultant is that they are more likely to decide that the clinical intention has been achieved before reaching the descending colon.